Οι Επτανήσιοι ποιητές στα νεοελληνικά αναγνώσματα της Μέσης Εκπαίδευσης: ιστορική παρουσίαση από το 1864 μέχρι το 1977 - (:unkn) unknown (My University, 2021)
Η διατριβή της φιλολόγου Φανής Μαγκούτα που εκπονήθηκε στο Τμήμα Ιστορίας του Ιονίου Πανεπιστημίου με τίτλο: «Οι Επτανήσιοι ποιητές στα νεοελληνικά αναγνώσματα της Μέσης Εκπαίδευσης: ιστορική παρουσίαση από το 1864 μέχρι το 1977» στηρίζεται σε δύο άξονες, όπως και από τον τίτλο καταδεικνύεται, στα σχολικά βιβλία για τη λογοτεχνία και στους ποιητές της Επτανήσου, μείζονες και ελάσσονες, που περιλαμβάνουν τα αναγνωστικά. Στο πρώτο μέρος της διατριβής εξετάζεται η πορεία του νεοελληνικού λόγου ως σχολικού αναγνώσματος, από το 1864 (Ένωση της Επτανήσου) μέχρι τις πύλες της εκπαιδευτικής μεταρρύθμισης του 1913/1914, ενώ στο δεύτερο μέρος μελετώνται διεξοδικά οι προοπτικές για την είσοδο των Επτανησίων ποιητών στα σχολικά εγχειρίδια. Οι συγγραφείς Γ. Δροσίνης και Γ. Κασδόνης, του πρώτου σχολικού εγχειριδίου για τη λογοτεχνία στα 1884, αξιοποιούν στα κείμενα που συλλέγουν ηθικές διηγήσεις και ωφέλιμες σκέψεις, που παραπέμπουν κατευθείαν στις Χρηστομάθειες για τις οποίες γίνεται λόγος στο πρώτο μέρος της διατριβής. Η παραπάνω διαπίστωση μας επιτρέπει να ανιχνεύσουμε, πριν από την έκδοση του πρώτου εγχειριδίου για τη λογοτεχνία (1884), «σπερματικές μορφές» του μαθήματος των Νέων Ελληνικών μέσα στις Χρηστομάθειες. Στις εννέα (09) σειρές των αναγνωστικών αποτυπώνεται η ιστορία της επτανησιακής ποίησης, με την παρουσία ή την απουσία ενδεχομένως, σε κάποιες σειρές των Επτανησίων ποιητών. Το έργο του Δ. Σολωμού στα βιβλία γνωστοποιείται και αναδεικνύεται από τις επιλογές του ανθολόγου Νικολάου Μπέρτου. Προβάλλεται ιδιαιτέρως από τον Αλέξανδρο Γ. Σαρή, διότι ο «Ύμνος εις την Ελευθερίαν» και τα «πατριωτικά» ποιήματα του Δ. Σολωμού είναι εθνικής σημασίας κείμενα. Μάλιστα, ο ανθολόγος Αλ. Γ. Σαρής αξιοποιεί στα εγχειρίδιά του και τον ιδιότυπο, στην ποιητική γραφή και στη γλώσσα, Ανδρέα Κάλβο, τον οποίο ο Κ. Παλαμάς ανέσυρε από την αφάνεια. Με συνειδητή πρόθεση, όπως είναι φυσικό, πραγματοποίησαν οι ανθολόγοι της Επτανήσου, επί παραδείγματι, οι Ι. Σ. Ζερβός, Χ. Αντωνάτος και Θ. Φιλιππάτος και Κ. Ρωμαίος, την προβολή των Επτανησίων ποιητών στα αναγνωστικά τους. Αξίζει να σημειωθεί ότι η αφομοίωση της Επτανησιακής ποίησης στον σχολικό λόγο πραγματοποιήθηκε διά των αναγνωστικών σε ποιότητες λεπτής απόχρωσης που αντιλαμβάνεται κανείς ρεαλιστικά. Εν τέλει, συνολικά, η θέση των ποιητών της Επτανήσου στη σχολική πράξη αποτιμάται θετικά.

Fanie Magouta’s doctoral dissertation at the Ionian University, Department of History, titled: “Ionian poets in Secondary Education literature textbooks from 1864 to 1977” is based on two pillars, as indicated by the title: school literature textbooks and the Ionian poets, both the famous and lesser-known ones, who have been included in the textbooks and have co-defined, in some way, their character. The first part of the dissertation explores the course of the modern Greek language as reading material in school, from 1864 (Union of the Ionian Islands with Greece) until the beginning of the 1913/14 educational reform. The second part provides an extensive study of the perspectives for the introduction of the Ionian poets into the school textbooks. The authors of the first school literature textbook (1884), G.Drosinis and G.Kasdonis, borrow much of the material for their book from Greek and foreign chrestomathies. More specifically, in the texts they collect, they make use of moral stories and useful reflections, that directly refer to chrestomathies. This realization allows us to detect in chrestomathies “embryonic forms” of the class of Modern Greek, before the publication of the first literature textbook (1884). Τhis publication is followed by nine (9) series of books of Modern Greek Readings [Neoellinika Anagnosmata]. Each series changes at the end of a four or five-year period, namely, when the time of approval of the books has expired, and new ones are introduced. The series are listed as follows: first series (1884-1909), second series (1909-1913), third series (1913-1917), fourth series (1917-1929), fifth series (1930-1938), sixth series (1938-1950), seventh series (1950-1956/57), eighth series (1956/57-1976/83), and ninth series (1983-2006). The history of Ionian poetry is captured in these series of textbooks, including or perhaps omitting in some of them, the Ionian poets. D. Solomos’ work in the books is communicated and brought out through the selections of Nikolaos Bertos. It is also featured by Al. G. Saris, because Solomos’ “Hymn to Freedom” and “patriotic poems” are texts of national significance. Moreover, in the textbooks, anthologist Al.G.Saris also makes use of the peculiar poetic writing and language of Andreas Kalvos, whom K. Palamas lifted out of obscurity. Understandably, Ionian anthologists introduced the Ionian poets in their textbooks intentionally. We mention for instance: I. S. Zervos (1917-1929) in the fourth series of schoolbooks, Ch. Antonatos and Th. Filippatos (1930-1938) and K. Romeos (1938-1950) in the sixth series. We should take into consideration that the lesser-known Ionian poets also determined the selections of the anthologists, for example G. Martinelis, St. Martzokis and Ger. Markoras, because their moral poems serve the purposes of the thematic units. The highly patriotic and prolific poet, Aristotelis Valaoritis, is widely anthologized both because of his influences from folk songs and because of his national spirit, which the schoolbooks preserve along with poetry’s moral dimension and Greekness. It is worth noting that, the assimilation of Ionian poetry into the school language, that occurred through the textbooks, is indeed evident in its qualities. Furthermore, it is mentioned that Athens, a Panhellenic literary centre, turned to the prominent Ionian poets Solomos and Kalvos, quite late. However, the course of the language issue in Greece vindicated the Ionian poets, because language was one of the determining factors of the form and character of the textbooks. In conclusion, the place of the Ionian poets, as a whole, in school practice is viewed positively.
Ionian poets in Secondary Education literature textbooks from 1864 to 1977
Keywords: Επτανήσιοι ποιητές, Τα Νεοελληνικά Αναγνώσματα, Χρηστομάθειες (1864-1884), Οι ανθολόγοι Νικ. Μπέρτος, Ν. Κοντόπουλος, Αλ. Γ. Σαρής, Ιστορία της εκπαίδευσης, Δημοτικισμός και Σχολικά βιβλία στα 1950, Κείμενα Νεοελληνικής Λογοτεχνίας, Τα "συλλογικά" Αναγνωστικά της 6ης σειράς (1938-1950), Η γλώσσα στην εκπαίδευση, Η αντιμετώπιση του γλωσσικού στα 1940, Ποιητές με επτανησιακή καταγωγή, Αρ. Βαλαωρίτης, Ν.Καββαδίας, Νάνος Βαλαωρίτης, Σονέτο - Λορ. Μαβίλης.; Ionian poets, school literature textbooks, chrestomathies, history of education (1864-1977), Nik. Bertos, Al. G. Saris, Modern Greek Readings [Neoellinika Anagnosmata] of G. Kalamatianos – Th. Makropoulos, N. Kontopoulos, demoticist movement and school textbooks in the 1950s, Modern Greek Literary Texts of N. Grigoriadis – D. Karvelis – Ch. Milionis – K. Balaskas – G. Paganos, nine series of literature textbooks, Soneto - Lor.Mabilis.